Live attenuated Mycobacterium bovis strains combined with the encapsulated H65 antigen as a vaccine strategy against bovine tuberculosis in a mouse model - Onnainty, Renée; Marini, María Rocío; Gravisaco, María José; Garcia, Elizabeth Andrea; Aagaard, Claus; Canal, Ana María; Granero, Gladys; Bigi, Fabiana; Blanco, Federico Carlos (Elsevier, 2024)
Mycobacterium bovis is an etiological agent of bovine tuberculosis (bTB) that also infects other mammals, including humans. The lack of an effective vaccine for the control of bTB highlights the need for developing new vaccines. In this study, we developed and evaluated an M. bovis strain deleted in the virulence genes phoP, esxA and esxB as a vaccine candidate against bTB in BALBc mice. The evaluated strains were the new live vaccine and BCG, alone or in combination with ncH65vD. The immunogen ncH65vD is a fusion protein H65, encapsulated together with vitamin D3, within the oily body of a nanocapsule composed of an antigen-loading polymeric shell. All vaccines conferred protection against the M. bovis challenge. However, no significant differences were detected among the vaccinated groups regarding bacterial loads in lungs and spleen. Mice vaccinated with the mutant strain plus ncH65vD showed negative Ziehl Neelsen staining of mycobacteria in their lungs, which suggests better control of bacteria replication according to this protection parameter. Consistently, this vaccination scheme showed the highest proportion of CD4 + T cells expressing the protection markers PD-1 and CXCR3 among the vaccinated groups. Correlation studies showed that PD-1 and CXCR3 expression levels in lung-resident CD4 T cells negatively correlated with the number of colony forming units of M. bovis in the lungs of mice. Therefore, the results suggest a link between the presence of PD-1 + and CXCR3 + cells at the site of the immune response against mycobacteria and the level of mycobacterial loads.